Effect of Total Amount of Metformin HCl on the Characteristics of Metformin-Ca Alginate Microspheres - Dewi Melani Hariyadi; Noorma Rosita; Tiara Jeni Rosadi (Universitas Airlangga, 2018)
Introduction: Metformin hydrochloride (metformin HCl) is an antidiabetic drug that is specifically used for type 2 diabetes mellitus (DM) and belongs to the biguanide antidiabetic drugs. Objective: The aim of this research was to determine the effect of total amount of metformin HCl on the characteristics of metformin HCl-Ca alginate microspheres using aerosolization technique. Methods: The total amount of metformin were 0.5 g (F1); 1 g (F2); 1.5 g (F3) and 2 g (F4). Drug was encapsulated into alginate and was crosslinked using CaCl2. Results: The results showed that drug loadings were 5.09%; 9.61%; 13.11%; and 15.09% respectively, while the entrapment efficiencies were 48.35%; 41.99%; 38.67%; and 30.53%. The yields were 80.92%; 74.12%; 68.27%; and 59.11% respectively. Based on the statistical analysis, it was found that there were significant differences between formulas. Particles of formulas decreased as the amount of drug increased. The resulting sizes were 1.82 Î¼m (F1); 1.96 Î¼m (F2); 2.1 Î¼m (F3); and 2.97 Î¼m (F4). Conclusion: It can be concluded that amount of drug significantly affected the characteristics of metformin-alginate microspheres.